FEATURES OF FANTASTIC WORKS (ON THE EXAMPLE OF THE WORKS OF RAY BRADBURY, ISAAC ASIMOV AND STEPHEN KING) - Usmonova, Zarina Habibovna (International Journal of Psychosocial Rehabilitation, 2020)
fiction is a genre based on the existence of an idea or factor that is impossible in the real world. Often there are many different genres and subgenres in which everyone finds something for themselves, providing fiction for a wide range of readers. This is such a huge variety that it is extremely difficult to choose one of the well-known authors of so many well-known authors. The list includes Isaac Asimov, Herbert Wells, Arkady and Boris Strugatsky, John Ronald Roel Tolkien, Robert Heinlin, Ray Bradbury, Stephen King, Dan Simmons, Joan Rowling, George Orwell and Aldous Hawksley.